Identifying HIF1A and HGF as two hub genes in aortic dissection and function analysis by integrating RNA sequencing and single-cell RNA sequencing data - Li, Hai-Bing; Liu, Chang; Mao, Xiang-Di; Yuan, Shu-Zheng; Li, Li; Cong, Xin (Frontiers in Cardiovascular Medicine, 2024)
Aortic dissection (AD) is a severe aortic disease with high mortality, and its pathogenesis remains elusive. In order to explore the regulatory mechanisms of AD, we integrated public RNA sequencing (RNA-seq) and single-cell RNA sequencing (scRNA-seq) datasets to screen the hub genes of AD and further analyzed their function, which may provide references to the diagnosis and treatment of AD. Methods: A variety of bioinformatics methods, including weighted gene co-expression network analysis, differential expression analysis, and protein-protein interactionwas, were used to screen hub genes. Quantitative real-time polymerase chain reaction was used to verify the expression of hub genes in beta-aminopropionitrile (BAPN)-induced mouse thoracic aortic aneurysm and dissection (TAAD) model. Results: A total of 71 overlapping genes were screened by intersecting the significant genes in pink module and the differentially expressed genes. A PPI network with 45 nodes and 74 edges was generated and 5 top hub genes (HIF1A, HGF, HMOX1, ITGA5, and ITGB3) were identified. All the hub genes had area under the curve values above 0.55. scRNA-seq data analysis showed that HIF1A was significantly up-regulated in macrophages and HGF was significantly up-regulated in vascular smooth muscle cells (SMCs) of the ascending aortas in AD patients. HIF1A may transcriptionally regulate multiple downstream target genes involving inflammation (TLR2, ALOX5AP, and MIF), glycolysis (ENO1, LDHA, and GAPDH), tissue remodeling (PLAU), and angiogenesis (SERPIN and VEGFA). HGF may participate in the signaling among SMCs, fibroblasts, and endothelial cells through binding to different receptors (MET, EGFR, IGF1R, and KDR). The mRNA expression of Hif1a, Hgf, and their target genes, including Alox5ap, Serpine1, Tlr2, Plau, Egfr, and Igf1r, were significantly up-regulated in aortic tissues of BAPN-treated mice. Conclusion: By integrating RNA-seq and scRNA-seq data, we identified HIF1A and HGF as two hub genes with good diagnostic efficiency for AD. HIF1A in macrophages may promote AD formation by promoting inflammation, glycolysis, tissue remodeling, and angiogenesis, and HGF may mediate signaling among SMCs, fibroblasts, and endothelial cells in the development of AD.